2015
DOI: 10.1111/jmwh.12217
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of How Midwives and Physicians Manage the Third Stage of Labor in the United States

Abstract: Surveys of third-stage labor practices must include large numbers of actions to represent what may be the state of US practices. Survey design may need to include a multiple-forms approach to avoid participant burden. Designs should include the exploration of differences by provider type as well as within provider variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 26 publications
(67 reference statements)
2
34
0
Order By: Relevance
“…The 23‐item survey was developed using the following process. First, a qualitative study and a review of the literature regarding labor practices formed the basis for the techniques and conditions included in the survey. There were 100 assessments, 110 interventions, and 65 “always used” activities previously identified .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 23‐item survey was developed using the following process. First, a qualitative study and a review of the literature regarding labor practices formed the basis for the techniques and conditions included in the survey. There were 100 assessments, 110 interventions, and 65 “always used” activities previously identified .…”
Section: Methodsmentioning
confidence: 99%
“…A previous qualitative study of certified nurse‐midwives (CNMs), certified professional midwives (CPMs), family practice physicians, and obstetricians in the United States was conducted to identify a provider‐generated list of interventions that may be used during the third stage of labor following a normal labor and birth . This study identified more than 110 interventions used by at least some practitioners
with variations within and between provider types . These variations demonstrated that many different techniques are used during the third stage of labor, including active and physiologic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…A national survey of nurse-midwives, certified professional midwives, family practice physicians, and obstetricians found that routine care during the third stage of labor included more than 100 identified practices. 25,26 These practice differences spanned environmental, maternal, medical or pharmacologic, and other components of care. In addition, it is unclear what effect lighting, noise (including phone or pagers), number of people present, or other birthing environmental variables have on physiologic completion of the third stage of labor.…”
Section: Discussionmentioning
confidence: 99%
“…More than 110 interventions, in addition to the components of AMTSL, have been reported as used during the third stage of labor in the United States . The use of these interventions varied within and between provider types.…”
Section: Introductionmentioning
confidence: 99%
“…7,15 More than 110 interventions, in addition to the components of AMTSL, have been reported as used during the third stage of labor in the United States. 16 The use of these interventions varied within and between provider types. The interventions fell into 4 distinct clusters of practices ranging from an essentially hands-off approach to a higherintervention approach.…”
Section: Introductionmentioning
confidence: 99%